Places of Physical Exercise as a Valuable Environment for Maintaining Physical and Intellectual Fitness of Older Persons - Ujma-Wąsowicz, Katarzyna (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
The need for leading an active life style, including amateur sport, which has a vital influence on our physical and intellectual fitness, should be obvious at present. Recent research of the Polish society indicates that generally the amount of exercise a person does, decreases with their age. It seems justified to ask the question about the roots of such a state of affairs. Is it a matter of bad habits? Or maybe our mentality? Or a lack of spatial conditions for doing sports at an older age? This paper concentrates on the last problem. It tries to answer this question on the basis of an analysis of the genesis of areas/facilities of physical activity for senior citizens and modern social and spatial conditions for the existence of such places. Further, the paper shows a description of noticeable trends of future development present in the environment of active seniors in the 21st century. In the summary, defines research directions which could positively influence the development of sport and recreation infrastructure in built environment friendly for older persons.